2010
DOI: 10.1177/1933719110377662
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of LOXL1 and HTRA1 Gene Expression in Endometriosis

Abstract: Endometriosis is a gynecologic disease characterized by the presence of endometrial tissue outside the uterine cavity. Although 15% of the female population in reproductive age is affected by endometriosis, its pathogenesis remains unclear. According to the most accepted pathogenesis hypothesis, endometrial fragments from the menstrual phase are transported through the uterine tubes to the peritoneal cavity, where they undergo implantation and growth, invading adjacent tissues. However, the establishment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 74 publications
0
18
0
1
Order By: Relevance
“…Accordingly, our group and others have described a significant association between PEX and systemic disorders of elastic tissues, that is, aortic aneurysms, coronary artery ectasia, renal artery stenosis and pelvic organ prolapse67839404142. Changes in LOXL1 gene expression have been observed in many other conditions, including aging4344 and disorders involving weakening of elastic connective tissues454647.…”
Section: Discussionmentioning
confidence: 90%
“…Accordingly, our group and others have described a significant association between PEX and systemic disorders of elastic tissues, that is, aortic aneurysms, coronary artery ectasia, renal artery stenosis and pelvic organ prolapse67839404142. Changes in LOXL1 gene expression have been observed in many other conditions, including aging4344 and disorders involving weakening of elastic connective tissues454647.…”
Section: Discussionmentioning
confidence: 90%
“…Other than cancer, migratory and invasive properties of endometrial epithelial cells were suggested to be responsible for endometriosis and adenomyosis (Chen et al, 2010;Dentillo et al, 2010;dos Santos Hidalgo et al, 2011). The main clinical features of endometriosis are pelvic pain and infertility (Giudice and Kao, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports an agreement on increased transcripts and protein levels for TAGLN gene in the disease (10)(11)(12)(13). It has been reported that the increased protein levels of transgelin is directly related to ectopic tissue and not to adjacent peritoneal tissue (10).…”
mentioning
confidence: 91%
“…Although the precise function of transgelin is still unknown, the protein is believed to be related to cell differentiation (2), cell migration (3,4), and the formation of podosomes (5) and involved in tissue invasion and matrix remodeling (6,7). Several studies have associated variations in the expression of the gene and its protein functions with diseases of benign and malignant natures, such as cancers (5,(8)(9)(10) and endometriosis (11)(12)(13). Endometriosis is characterized by ectopic endometrial tissue (14).…”
mentioning
confidence: 99%